The Meaning of Ustadz Hanan Attaqi’s Persuasive Rhetoric Through the TikTok Platform @ayah_amanah in Building the Spiritual Obedience of Generation Z - Nasichah N; Sa’adah S; Naila Zhafira Rasid (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study was motivated by the phenomenon of digital preaching that is rapidly growing among Generation Z, particularly through the TikTok platform. The purpose of this study is to analyze the influence of Ustadz Hanan Attaqi's persuasive rhetoric on increasing the compliance and spiritual awareness of Generation Z on social media. The research uses a descriptive qualitative approach with a constructivist paradigm and cultural phenomenology method. Data were obtained through observation of preaching content on TikTok, analysis of audience interactions (likes, comments, and reposts), and an online survey of 105 respondents aged 15–20 years who belong to Generation Z. The results show that 94.3% of respondents feel that Ustadz Hanan Attaqi's preaching has a positive impact on self-introspection, increased consistency in worship, and strengthening of morals. This effectiveness is influenced by the application of persuasive rhetoric that combines ethos, pathos, and logos in a balanced manner, delivered in a communicative style that is relevant to the lives of young people. This research contributes to the development of digital da'wah communication and demonstrates that social media can be an effective tool in shaping the spirituality of the younger generation in the modern era.